The Effect Of Glucose Concentration On The Biotransformation Of Valencene To Nootkatone - Heah, Joo Yee (Universiti Sains Malaysia, 2022)
Nootkatone is an organic compound which has a unique aroma with valencene as the substrate for nootkatone production that is commonly synthesised through a chemical reaction. However, the chemical synthesis process involved the usage of heavy metals as catalysts to oxidize the double bond in valencene. Therefore, a non-pathogenic yeast named Yarrowia lipolytica is suggested to replace the heavy metals catalyst. The usage of yeast allows the nootkatone products to meet their natural properties. In addition, it is more sustainable as heavy metals are usually rarely found naturally on the Earth, so by reducing their usage, we can ensure that future generations meet their own needs. Plus, if the heavy metals do not dispose of properly, they will cause contamination to the Earth, which will harm the environment. Using Y. lipolytica in the biotransformation step, nootkatone can be produced from valencene with the optimum glucose concentration in LB media as 15 g/L. The nootkatone amount reaches the highest when the valencene is at the highest concentration. But the nootkatone peak does not come out for certain samples. This might be due to several reasons, such as the pore size of the yeast’s cell membrane is too small for nootkatone to diffuse out from the cell, the nootkatone level is too low to be diffused out, some of the yeasts might die, and gas chromatography is not ideally operated. Therefore, sonication is recommended to break the cells to allow nootkatone to release from the cells.